Psychosocial and emotional well-being of Syrian refugee children and adolescents in Jordan: In-camp versus out-of-camp comparative analysis - Yonis, Othman B.; Khader, Yousef; Taha, Hana; Al-Madhwahi, Ahmed; Khudair, Sara A.; Tanaka, Eizaburo; Al Nsour, Mohannad (Narra J, 2024)
There is a notable gap in understanding how different living arrangements influence the psychosocial and emotional well-being of Syrian refugee children and adolescents. Moreover, limited literature exists on the comparison between in-camp and out-of-camp living situations. The aim of this study was to compare the psychosocial and emotional status between camp and non-camp Syrian refugee children and adolescents living in Jordan. A nationwide school survey was conducted in Jordan from December 2022 to April 2023 and targeted children (8–11 years) and adolescents (12–18 years), encompassing Jordanians, Syrians, and Palestinians, both in camps (camp refugees) and urban areas (urban refugees). In this paper, the analysis was limited to Syrian refugees.  A total of 1,420 children and 1,249 adolescents were included. Children in camps had higher rates of hyperactivity (12.7% vs 8.3%) and total difficulties (19.3% vs 13.9%) compared to urban dwellers. However, they had lower rates of bedtime problems (12.8% vs 17.0%) and problematic internet use (19.9% vs 34.8%). Camp adolescents had higher rates of separation anxiety disorder (44.0% vs 37.8%) and conduct problems (22.2% vs 15.0%), but lower rates of poor physical functioning (43.3% vs 52.3%) compared to urban adolescents. Adjusted analysis showed lower odds of generalized anxiety disorder (OR=0.59), problematic internet use (OR=0.39), and bedtime problems (OR=0.67) for camp children. However, they had higher odds of emotional symptoms (OR=1.47), hyperactivity (OR=2.08), and overall difficulties (OR=1.50). Camp adolescents had higher odds of overall difficulties (OR=1.49) but lower odds of poor physical functioning (OR=0.67) compared to urban adolescents. In conclusion, children in refugee camps had lower rates of problematic internet use and bedtime issues but higher rates of hyperactivity and overall difficulties than urban children. Similarly, camp adolescents faced more total difficulties but reported better physical functioning than their urban peers. The complex interplay between living conditions and well-being underscores the need for tailored mental health interventions for displaced populations.